A Case study of Classroom management at English Education Deparment of STKIP Muhammadiyah Enrekang: Students’s Team Work Preference - Umiyati Jabri; Ita Sarmita Samad (Edumaspul: Jurnal Pendidikan, 2019)
This study aims to identify students’ teamwork models that the students prefer in the teaching and learning process in the classroom For this study, a 10-item possitive–negative statements questionnaire was constructed and gave to the students. The questionnaire was completed by 60 students. From the data analyzing using a Likert scale, the result of the questionnaire calculation showed that the students’ average is about 27, 6. This result is in undecided categories as stated on the Likert scale. It means that the students cannot decide their teamwork model preferences from teamwork models that lecturers applied in teaching and learning English in the classroom. Thus, it can be assumed that whatever the teamwork model implemented by lecturers in the teaching and learning process in the classroom, the students can receive it. In other words, students still have a positive attitude toward whatever the teamwork model implemented by the lecturers in the teaching and learning process in the classroom.